DEVELOPMENT OF ANALYTICAL METHOD FOR IDENTIFICATION OF SIBUTRAMINE HCL IN TRADITIONAL MEDICINE USING SOLID PHASE EXTRACTION – HIGH PERFORMANCE LIQUID CHROMATOGRAPHY - Kamardi, Tarita (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Object: The purpose of this study is to develop a rapid and sensitive method for identifying sibutramine HCl. Methods: Reversed phase solid phase extraction (SPE) method with Hydrophilic-Lipophilic Balance (HLB) cartridge was selected to be developed and optimized. Optimization was done by optimizing solvent in sample preparation and rinse solvent in washing step. The extract of SPE was injected into reversed phase HPLC with C18 column with PDA detector. Furthermore, the optimized results was validated which included specificity and determination of the detection limit. Validated analytical method was used to analyze sibutramine HCl qualitatively in slimming herbal medicine which was obtained from the market. Results: Analysis method optimization results showed that the optimum sample solvent to extract sibutramine HCl in solid phase extraction was 3% orthophosphoric acid. Then it was shaken for 30 min and filtered, the filtrate was put in SPE cartridge that had been conditioned using ethanol and water. After rinsing with NH4OH solution in water and NH4OH solution in 80% ethanol, the analyte was eluted with acetonitrile. Identification of sibutramine HCl was done by HPLC at wavelength 254 nm. Sibutramine HCl gave maximum wavelength at 222 nm. Sibutramine HCl calibration curve gave quite linear results in the range from 0.10 to 0.50 mg/ml with R2 = 0.9966. The detection limit of this assay was 2.326 µg/ml. Specificity of this method is quite good. Simulation sample gave resolution for diethylpropion 2.415; sibutramine HCl 2.877 and amphetamine sulfate 5.673.This methods recovery was 38.0 to 45.0 %. Conclusion: This study showed faster and specific method for identifying sibutramine HCl in traditional medicine. Keywords: sibutramine HCl, solid phase extraction, HLB, slimming herbal medicine, HPLC